Research Progress on the Effects of Selenium on the Growth and Quality of Tea Plants - Juan Xiang; Shen Rao; Qiangwen Chen; Weiwei Zhang; Shuiyuan Cheng; Xin Cong; Yue Zhang; Xiaoyan Yang; Feng Xu (Plants, 2022)
Selenium (Se) is an essential trace element for humans and animals, and it plays an important role in immune regulation and disease prevention. Tea is one of the top three beverages in the world, and it contains active ingredients such as polyphenols, theanine, flavonoids, and volatile substances, which have important health benefits. The tea tree has suitable Se aggregation ability, which can absorb inorganic Se and transform it into safe and effective organic Se through absorption by the human body, thereby improving human immunity and preventing the occurrence of many diseases. Recent studies have proven that 50~100.0 mg/L exogenous Se can promote photosynthesis and absorption of mineral elements in tea trees and increase their biomass. The content of total Se and organic selenides in tea leaves significantly increases and promotes the accumulation of polyphenols, theanine, flavonoids, and volatile secondary metabolites, thereby improving the nutritional quality of tea leaves. This paper summarizes previous research on the effects of exogenous Se treatment on the growth and quality of tea trees to provide a theoretical basis and technical support for the germplasm selection and exploitation of Se-rich tea.